Reconnecting State and Kinship. - Thelen, Tatjana (University of Pennsylvania Press, Inc., 2017)
Reconnecting State and Kinship seeks to overcome the traditional dichotomy between state and kinship, asking whether concepts associated with one sphere surface in the other, tracking the evolution of these concepts through time and space, and exploring how this binary is reinforced within the social sciences.